Experimental peri-implantitis induces neuroinflammation: An exploratory study in rats - Emilio A. Cafferata; Ausra Ramanauskaite; Astrid Cuypers; Karina Obreja; Eva Dohle; Shahram Ghanaati; Frank Schwarz (BMC, 2024)
Abstract Purpose Cumulating evidence supports the close association between periodontal diseases, neuroinflammation and neurodegenerative pathologies, except for peri-implantitis (PI). Thus, this study explored the association between experimental PI and neuropathological changes in the rat brain. Materials and methods After bilateral first molars extraction, experimental PI was induced at titanium implants placed in the maxillae by lipopolysaccharide injections and ligature placement. Following 28-weeks of disease progression, the maxillae and brains were retrieved from 6 rats. Healthy brains from 3 rats were used as control. Brains were analyzed by immunohistochemistry to detect signs of neuroinflammation (interleukin (IL)-6 and tumor necrosis factor (TNF)-α)), microglial activation (IBA-1) and astrogliosis (GFAP). To explore signs of neurodegeneration, hematoxylin/eosin and Nissl stainings were used. Also, four different antibodies against amyloid beta (Aβ 1-42) were tested. Results Chronic PI lesions showed peri-implant bone resorption accompanied by large inflammatory infiltrates. IL-6+ and TNF-α+ cells were found within the CA1 and Dentate Gyrus regions of the hippocampus of the PI-affected group, while almost no immune-positivity was detected in the control (p < 0.05). Detection of activated GFAP+ microglia and IBA-1+ astrocytes surface were significantly higher at the CA areas, and cerebral cortex of the PI-affected group, in comparison with control (p < 0.05). Shrunk neurons with pyknotic nuclei were inconsistently found among the PI-affected group, and these were almost not detected in control. No positive Aβ reactivity was detected in any of the samples. Conclusion Chronic experimental PI lesions led to an increased detection of IL-6 and TNF-α, GFAP+ microgliosis and IBA-1+ astrocytosis, and in some cases, neurodegeneration, in the rat brain.